Catalyst, process for its preparation and use

CN122879747APending Publication Date: 2026-10-09TIANJIN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610882440.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,受限于相关技术,目前的电催化一氧化氮还原反应的效率较低

Benefits of technology

[0013]根据本公开实施例提供的催化剂,通过向铜纳米线中引入取代铜的过渡金属掺杂原子,调控了铜的电子结构,增强了水解离产生活性氢的能力,同时促进了NO的吸附与加氢过程,从而弥补了纯铜表面活性氢不足的本征缺陷,显著提升了电催化一氧化氮还原合成氨的产氨速率和法拉第效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879747A_ABST
    Figure CN122879747A_ABST
Patent Text Reader

Abstract

The present disclosure provides a catalyst and a preparation method and application thereof. The catalyst comprises: a substrate, the substrate comprising copper nanowires; a doping metal, the doping element replacing at least part of copper in the copper nanowires, the doping metal comprising a transition metal. By introducing transition metal doping atoms to replace copper in the copper nanowires, the electronic structure of copper is regulated, the activity of hydrogen produced by water splitting is enhanced, and the adsorption and hydrogenation process of NO is promoted, thereby making up for the intrinsic defects of insufficient active hydrogen on the pure copper surface, and significantly improving the ammonia production rate and Faraday efficiency of electrocatalytic reduction of nitric oxide to synthesize ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of catalysis technology, specifically to catalysts, their preparation methods, and applications. Background Technology

[0002] Nitric oxide (NO) primarily originates from industrial emissions, vehicle exhaust, and thermal power generation. NO causes a range of environmental problems, including photochemical smog, acid rain, and ozone layer depletion, seriously threatening human health. Selective catalytic reduction (SCR) is currently the most widely used NO removal technology, converting toxic NO into inert nitrogen gas. However, this process consumes ammonia (NH3), a valuable chemical. In contrast, electrocatalytic nitric oxide reduction (NORR) utilizes renewable electricity and water as the sole hydrogen source, providing a pathway for the sustainable synthesis of NH3 and avoiding the high energy consumption of traditional processes. However, due to technological limitations, the efficiency of current electrocatalytic nitric oxide reduction reactions is relatively low. Summary of the Invention

[0003] In view of this, the present disclosure provides a catalyst, its preparation method, and its application.

[0004] The first aspect of this disclosure provides a catalyst, comprising: The substrate includes copper nanowires; Doped metals are elements that replace at least a portion of the copper in copper nanowires. Doped metals include transition metals.

[0005] In one embodiment, copper nanowires are cross-linked to form a network structure; Preferably, the mesh structure encloses at least one hole; Preferably, the pore size is 10 nm-100 nm.

[0006] In one embodiment, the transition metal includes at least one of Ni, Co, Fe, and Zn; Preferably, the ratio of the number of moles of the doped metal to the sum of the number of moles of the doped metal and the number of moles of copper is greater than or equal to 1:100 and less than or equal to 12:100.

[0007] In one embodiment, the length of the copper nanowire is greater than or equal to 5 μm and less than or equal to 8 μm; Preferably, the diameter of the copper nanowire is greater than or equal to 20 nm and less than or equal to 30 nm.

[0008] The second aspect of this disclosure provides a method for preparing the catalyst provided in the first aspect, comprising: A precursor solution is obtained by dispersing copper salt, salt of doped metal, reducing agent and surfactant in water; The precursor solution is heated to undergo the first reaction, yielding the catalyst.

[0009] In one embodiment, the copper salt comprises anhydrous copper chloride, and the metal-doped salt comprises a hydrate of the metal-doped chloride; the reducing agent comprises at least one of glucose, ascorbic acid, and ethylene glycol, and the surfactant comprises at least one of hexadecylamine, oleylamine, and octadecylamine. In one embodiment, the first reaction temperature is greater than or equal to 100°C and less than or equal to 200°C, and the reaction time is greater than or equal to 12 hours and less than or equal to 30 hours.

[0010] In one embodiment, the crude product obtained from the first reaction is centrifuged and washed sequentially to obtain the catalyst; Preferably, the centrifugation speed is greater than or equal to 7000 rpm and less than or equal to 9000 rpm; Preferably, anhydrous ethanol and n-hexane are used for washing.

[0011] In one embodiment, the washed crude product is dried to obtain the catalyst; Preferably, the drying temperature is greater than or equal to 30°C and less than or equal to 50°C; the drying time is greater than or equal to 10 hours and less than or equal to 14 hours.

[0012] The third aspect of this disclosure provides the use of the catalyst provided in the first aspect in the electrocatalytic reduction of nitric oxide to ammonia.

[0013] According to the catalyst provided in the embodiments of this disclosure, by introducing transition metal doping atoms that replace copper into copper nanowires, the electronic structure of copper is regulated, the ability of water dissociation to generate active hydrogen is enhanced, and the adsorption and hydrogenation process of NO is promoted. This compensates for the intrinsic defect of insufficient active hydrogen on the surface of pure copper, and significantly improves the ammonia production rate and Faraday efficiency of electrocatalytic nitric oxide reduction to ammonia synthesis. Attached Figure Description

[0014] Figure 1 This is a schematic diagram of the catalyst preparation method in one embodiment of the present disclosure.

[0015] Figure 2 The image shows the XRD pattern of the catalyst in Example 1.

[0016] Figure 3 This is a SEM image of the catalyst in Example 1.

[0017] Figure 4 The graph shows the ammonia production rate and potential relationship of the catalyst used in Example 2 for electrocatalytic reduction of nitric oxide to ammonia.

[0018] Figure 5The graph shows the Faraday efficiency and potential relationship of the catalyst in Example 2 for the electrocatalytic reduction of nitric oxide to ammonia. Detailed Implementation

[0019] The technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments of this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure.

[0020] Furthermore, to better illustrate this disclosure, numerous specific details are set forth in the following detailed description. Those skilled in the art will understand that this disclosure can be practiced without certain specific details. In some instances, methods and means well-known to those skilled in the art have not been described in detail in order to highlight the main points of this disclosure.

[0021] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0022] Furthermore, the terms "first" and "second" are used only to distinguish descriptions and should not be interpreted as indicating or implying relative importance.

[0023] In this disclosure, "matrix" refers to the continuous phase material that constitutes the main framework of the catalyst and serves as the support for the doped metal. For example, it may include, but is not limited to, copper nanowires, nanorods, or nanosheets, especially copper nanowires with a one-dimensional morphology, or networks formed by their aggregation.

[0024] In this disclosure, "copper nanowire" refers to a slender copper elemental structure with at least one dimension at the nanometer or micrometer scale, whose length is significantly greater than its cross-sectional size, and which can provide a high specific surface area and electron transport path for the reaction.

[0025] In this disclosure, "doped metal" refers to a heterogeneous metal element that is intentionally introduced into the matrix lattice to regulate the electronic structure and catalytic performance of the matrix, wherein its atoms partially replace the matrix metal atoms.

[0026] In this disclosure, "uniform doping" refers to the dispersion of doped metal atoms at the atomic or nanoscale within the overall volume of the matrix, without the formation of detectable independent doped metal phases or surface enrichment layers. For example, no independent diffraction peaks or phase separation regions of the doped metal are observed by transmission electron microscopy (SEM) and X-ray diffraction (XRD).

[0027] In this disclosure, "crosslinking to form a network structure" refers to the interconnection of multiple copper nanowires through physical contact or van der Waals forces to form a three-dimensional porous network. For example, this may include, but is not limited to, a continuous porous electrode structure formed by the spontaneous interweaving and overlapping of nanowires during the fabrication process. "Pore" may refer to the voids enclosed by the network structure, with dimensions ranging from nanometers to micrometers, to facilitate mass transfer of reactants.

[0028] In this disclosure, "transition metal" refers to metallic elements in the periodic table that have incomplete d orbitals in the d-block or ds-block.

[0029] In this disclosure, "reducing agent" refers to any chemical reagent that provides electrons in a precursor solution to reduce metal ions to zero-valent metals.

[0030] In this disclosure, "electrocatalytic reduction of nitric oxide to ammonia" refers to an electrochemical process in which nitric oxide molecules are reduced to ammonia on a cathode surface under the drive of an applied electric field, using water as a hydrogen source. For example, this may include, but is not limited to, using the catalyst of this disclosure as a cathode in an alkaline medium to electroreduc dissolved NO gas to NH3.

[0031] In related technologies, the electrocatalytic reduction of nitric oxide to ammonia can utilize renewable electricity to convert nitric oxide into ammonia, which helps to realize the resource utilization of pollutants. However, copper-based catalysts generally suffer from low ammonia production activity and Faraday efficiency in this reaction. Through in-depth research, the inventors of this disclosure have discovered that the main reason for these problems is the insufficient ability of copper itself to generate active hydrogen through water dissociation, and the difficulty in effectively matching the adsorption strength of nitric oxide with the subsequent hydrogenation process, resulting in limited active hydrogen supply and low intermediate conversion efficiency. To solve this problem, this disclosure proposes uniformly doping a non-noble metal element into a copper nanowire matrix. By introducing d-band centers through metal doping to adjust the electronic structure of copper, the adsorption energy of nitric oxide at copper sites can be optimized. Simultaneously, the doped metal sites can promote the dissociation of water in alkaline media, generating sufficient active hydrogen. The active hydrogen and the hydrogenation sites on copper then couple, thereby synergistically improving the reaction rate and selectivity of ammonia synthesis.

[0032] Based on the above concept, a first aspect of this disclosure provides a catalyst comprising: a matrix and a doped metal. The matrix comprises copper nanowires; the doped metal comprises a transition metal, wherein the dopant element replaces at least a portion of the copper in the copper nanowires.

[0033] According to the catalyst provided in the embodiments of this disclosure, by introducing transition metal doping atoms that replace copper into copper nanowires, the electronic structure of copper is regulated, the ability of water dissociation to generate active hydrogen is enhanced, and the adsorption and hydrogenation process of NO is promoted. This compensates for the intrinsic defect of insufficient active hydrogen on the surface of pure copper, and significantly improves the ammonia production rate and Faraday efficiency of electrocatalytic nitric oxide reduction to ammonia synthesis.

[0034] As can be understood, a copper nanowire matrix refers to a material with copper as the main metallic component, possessing a one-dimensional linear morphology and a diameter at the nanoscale. The transition metal includes at least one of Ni, Co, Fe, and Zn, which is uniformly doped into the copper lattice. Uniform doping means that the transition metal is distributed atomically or forms a solid solution phase throughout the entire volume of the copper nanowire, rather than existing as discrete second-phase particles or surface coatings. This uniform doping avoids the formation of separated metallic phases or agglomerations, ensuring that the doped metal atoms interact electronically with copper atoms at the lattice scale to the maximum extent.

[0035] For example, the introduction of doped metals enhances catalytic performance through two main mechanisms. First, the electronic interaction between the doped metal and copper causes a shift in the d-band center of copper, thereby modulating the adsorption energy of nitric oxide molecules on the catalyst surface, bringing it closer to the optimal adsorption strength required for hydrogenation, which is beneficial for nitric oxide adsorption and subsequent activation. Second, the doped metal sites have a lower reaction energy barrier for water dissociation in alkaline electrolytes, which can efficiently promote water dissociation to generate active hydrogen, compensating for the insufficient water dissociation capacity of pure copper surfaces. These active hydrogens then migrate to the copper sites and undergo hydrogenation with the adsorbed nitric oxide, gradually generating ammonia. This synergistic effect effectively solves the problem of insufficient activity and selectivity in ammonia production of copper-based catalysts.

[0036] In one embodiment, copper nanowires are cross-linked to form a network structure. Optionally, the network structure encloses at least one pore. The network structure contains micron-scale channels and nanoscale gaps, which facilitates the wetting of the electrolyte into the active sites and the diffusion of the reactant nitric oxide, while also aiding in the timely removal of the product ammonia, thereby improving mass transfer efficiency.

[0037] Optionally, the pore size is 10 nm-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc. It can be understood that the pore size can be the diameter of the pore, the average diameter of the pore, the actual diameter of the pore, the minimum diameter of the pore, or the maximum diameter of the pore. When the pore size is greater than 100 nm, the specific surface area decreases significantly, the density of active sites decreases, leading to a decrease in the ammonia production rate and Faraday efficiency. When the pore size is less than 10 nm, the pores are too small, resulting in a sharp increase in mass transfer resistance, making it difficult for nitric oxide and reaction intermediates to diffuse effectively to the active sites, and pore blockage easily occurs, thereby inhibiting the catalytic reaction and reducing the performance of ammonia synthesis.

[0038] For example, the mesh structure encloses at least one pore, the size of which may not be uniform and may fluctuate in the range of 10 nm to 100 nm.

[0039] In one embodiment, the length of the copper nanowires is greater than or equal to 5 μm and less than or equal to 8 μm, for example, it can be 5 μm, 6 μm, 7 μm, or 8 μm. This length range allows the copper nanowires to construct a hierarchical porous network structure through physical cross-linking between the wires when forming a catalyst layer or cathode film. The hierarchical porous network contains micron-scale channels and nanoscale gaps, which is beneficial for the wetting of the electrolyte to the active sites and the diffusion of the reactant nitric oxide, while also facilitating the timely removal of the product ammonia, thereby improving mass transfer efficiency. When the length of the copper nanowires is significantly less than 5 μm, the degree of overlap and cross-linking between the wires is insufficient, resulting in a low density of the formed electrode structure and excessively large pore size, which is not conducive to constructing a continuous electron transport network and sufficient electrode mechanical integrity. When the length of the copper nanowires is significantly greater than 8 μm, the copper nanowires are prone to excessive entanglement, resulting in uneven pore distribution, increased local mass transfer resistance, and also reduced catalytic efficiency.

[0040] Optionally, the diameter of the copper nanowires is greater than or equal to 20 nm and less than or equal to 30 nm, for example, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, etc. When the diameter of the copper nanowires is greater than 30 nm, the specific surface area is significantly reduced, resulting in insufficient exposed active sites and a decrease in the ammonia production rate and Faradaic efficiency of the electrocatalytic reduction of nitric oxide to ammonia. When the diameter of the copper nanowires is less than 20 nm, the nanowire structure becomes less stable and prone to aggregation or breakage.

[0041] In one embodiment, the ratio of the molar number of the doped metal to the sum of the molar number of the doped metal and the molar number of copper is greater than or equal to 1:100 and less than or equal to 12:100. For example, this molar ratio can be 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, or 12:100. Within this range, the doped metal can effectively regulate the electronic structure of copper without causing the precipitation of independent metallic phases or the formation of obvious enrichment regions due to excessive doping. When the molar ratio is less than 1:100, the doped metal content is too low, the electronic structure regulation effect is weak, the density of water dissociation active sites is insufficient, and the improvement on ammonia production activity and Faraday efficiency is not significant. When the molar ratio is greater than 12:100, the doped metal may locally accumulate in the copper matrix, or even form discrete metal phases or agglomerates. This will not only reduce the effective utilization rate of the active component, but may also destroy the continuity and conductivity of the copper nanowires, and may introduce side reaction active sites that are not conducive to the hydrogenation of nitric oxide, resulting in a decrease in ammonia production selectivity.

[0042] For example, this disclosure optimizes the NO adsorption strength by modulating the electronic structure of Cu through non-noble metal doping; simultaneously, the introduction of non-noble metal sites promotes the kinetics of water dissociation to generate active hydrogen in alkaline media, significantly improving NORR performance. This synergistic effect effectively alleviates the intrinsic deficiency of insufficient active hydrogen on the Cu surface.

[0043] The second aspect of this disclosure provides a method for preparing the catalyst provided in the first aspect, referring to... Figure 1 The diagram shows a process flow chart for preparing the catalyst, which includes the following steps.

[0044] S100: Copper salt, salt of doped metal, reducing agent and surfactant are dispersed in water to obtain a precursor solution.

[0045] In one embodiment, the copper salt includes anhydrous copper chloride, and the metal-doped salt includes a hydrate of a metal-doped chloride; the reducing agent includes at least one of glucose, ascorbic acid, and ethylene glycol, and the surfactant includes at least one of hexadecylamine, oleylamine, and octadecylamine.

[0046] For example, dispersing copper salt, doped metal salt, reducing agent, and surfactant in water includes the following steps: dissolving copper salt, doped metal salt, reducing agent, and surfactant in ultrapure water and stirring until homogeneous to obtain a precursor solution. The copper salt can be, for example, anhydrous copper chloride, and the doped metal salt can be, for example, a hydrate of a doped metal chloride, such as nickel chloride hexahydrate, cobalt chloride hexahydrate, ferric chloride hexahydrate, or zinc chloride hexahydrate. The reducing agent can be glucose, and the surfactant can be hexadecylamine. Glucose has mild reducing properties under high-temperature hydrothermal conditions and can gradually reduce Cu and the doped metal to their metallic state. Hexadecylamine acts as a surface covering agent and complexing agent; the amino groups in its molecules can selectively adsorb onto the (100) crystal plane of copper, inhibiting the growth of this crystal plane, thereby guiding the crystal to grow one-dimensionally anisotropically along the (100) direction to form nanowires; simultaneously, hexadecylamine can also complex with metal ions, stabilizing the metal ions in the precursor solution and ensuring that the doped metal atoms uniformly enter the copper lattice during the co-reduction process.

[0047] S200: Heating the precursor solution causes the first reaction to produce the catalyst.

[0048] In one embodiment, the first reaction temperature is greater than or equal to 100°C and less than or equal to 200°C, and the reaction time is greater than or equal to 12 h and less than or equal to 30 h. For example, the hydrothermal reaction temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C. The reaction time can be 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, or 30 h. When the first reaction temperature is below 100°C, the reducing power of glucose is insufficient, the reduction rate of metal ions is slow, it is difficult to form well-structured nanowires, and the co-reduction efficiency of the doped metal is low. When the first reaction temperature is above 200°C, the reaction is too vigorous, which may lead to uncontrollable nanowire morphology, the appearance of particulate byproducts, or widening of the nanowire diameter. When the first reaction time is less than 12 h, the reduction and crystal growth are insufficient, and the aspect ratio of the nanowires is too small; when the first reaction time is longer than 30 h, the nanowires may overgrow and become entangled, affecting the uniformity of the subsequent electrode structure.

[0049] In one embodiment, the crude product obtained from the first reaction is centrifuged and washed sequentially to obtain the catalyst. Optionally, the centrifugation speed is greater than or equal to 7000 rpm and less than or equal to 9000 rpm (e.g., 7000 rpm, 8000 rpm, 9000 rpm, etc.); optionally, washing is performed with anhydrous ethanol and n-hexane.

[0050] For example, after cooling the crude product obtained from the first reaction, the resulting suspension is centrifuged and washed sequentially with an organic solvent. For instance, centrifugation can be performed at 8000 rpm, followed by washing with anhydrous ethanol and n-hexane until the supernatant is clear. Anhydrous ethanol is used to remove residual water-soluble impurities and unreacted glucose, while n-hexane is used to remove organic surfactants such as hexadecylamine.

[0051] In one embodiment, the washed crude product is dried to obtain the catalyst.

[0052] Optionally, the drying temperature is greater than or equal to 30°C and less than or equal to 50°C (e.g., 30°C, 40°C, or 50°C, etc.); the drying time is greater than or equal to 10 hours and less than or equal to 14 hours (e.g., 10 hours, 12 hours, or 14 hours, etc.).

[0053] The Cu nanowires disclosed herein are prepared via a crystal facet-selective synthesis strategy. Hexadecylamine is used as a surfactant, selectively adsorbing onto the Cu(100) crystal facet to promote anisotropic growth of the nanowires. Glucose, as a reducing agent, slowly reduces metal ions at high temperature, forming a uniform nanowire morphology. The introduction of non-noble metals is achieved through a one-step hydrothermal method, where non-noble metal ions are co-reduced with copper ions during the reaction. During the preparation process, hexadecylamine not only acts as a surface covering agent to control crystal facet growth but also as a complexing agent to stabilize metal ions, ensuring the uniformity and reproducibility of the nanowire structure. It can be understood that the above-mentioned non-noble metal-doped copper nanowire catalyst can be prepared via a one-step hydrothermal co-reduction method. This preparation method can simultaneously reduce and incorporate dopant metal atoms into the copper lattice while forming copper nanowires, achieving simultaneous anisotropic growth and uniform elemental doping. The process is simple and highly controllable.

[0054] The third aspect of this disclosure provides the use of the catalyst provided in the first aspect in the electrocatalytic reduction of nitric oxide to ammonia.

[0055] For example, the catalyst can be used as a cathode material for the electrocatalytic reduction of nitric oxide to ammonia.

[0056] The present disclosure will be further described below with reference to specific embodiments. It should be noted that the following embodiments are only used to explain the present disclosure and should not be construed as limiting the present disclosure.

[0057] Example 1 The preparation of the catalyst includes the following steps: 1. Dissolve 1.17 mmol anhydrous copper chloride, 0.13 mmol nickel chloride hexahydrate, 0.2 g glucose, and 1.34 g hexadecylamine in 100 mL of ultrapure water. The ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution is 10:100. Stir vigorously at room temperature for 12 h until the solution turns a uniform sky blue color.

[0058] 2. Transfer the above mixed solution to a 100 mL polytetrafluoroethylene liner, place it in the reaction vessel and tighten it, and react in a 100℃ forced-air oven for 24 h.

[0059] 3. After the reaction is complete, cool the solution with cold water for 1 hour, remove the suspension and centrifuge at 8000 rpm. Wash the suspension with anhydrous ethanol and n-hexane until the supernatant is clear.

[0060] 4. The precipitate was dried in an oven at 40°C for 12 h to obtain the catalyst.

[0061] Figure 2 The X-ray diffraction (XRD) curve of the obtained catalyst; from Figure 2 It can be seen that there are three characteristic diffraction peaks at 43.3°, 50.4° and 74.1°, which correspond to the (111), (100) and (110) crystal planes of Cu, respectively. However, no diffraction peaks of Ni were observed, which may be due to the low content of Ni. Figure 2 The image shows a scanning electron microscope (SEM) image of the obtained Ni-doped Cu nanowire catalyst. Figure 3 The successful fabrication of nanowires with lengths ranging from 5 μm to 8 μm can be clearly observed.

[0062] Example 2 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 120℃ forced-air oven for 24 h.

[0063] Figure 4 and Figure 5 This is a graph showing the activity data of the catalyst obtained in this embodiment as a cathode material for the electrocatalytic reduction of nitric oxide to ammonia; (The graph is from...) Figure 4 and Figure 5 It can be seen that the optimal ammonia production rate is 6.84 mmol h⁻¹. -1 cm -2 It has a Faraday efficiency of 90.35% and exhibits excellent ammonia synthesis activity.

[0064] Example 3 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 160℃ forced-air oven for 24 h.

[0065] Example 4 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 200℃ forced-air oven for 24 h.

[0066] Example 5 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 120℃ forced-air oven for 12 h.

[0067] Example 6 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 120℃ forced-air oven for 16 h.

[0068] Example 7 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 120℃ forced-air oven for 20 h.

[0069] Example 8 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 120℃ forced-air oven for 30 h.

[0070] Example 9 The preparation method of the catalyst is basically the same as in Example 2, except that the ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution in step 1 is 1:100.

[0071] Example 10 The preparation method of the catalyst is basically the same as in Example 2, except that the ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution in step 1 is 2:100.

[0072] Example 11 The preparation method of the catalyst is basically the same as in Example 2, except that the ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution in step 1 is 4:100.

[0073] Example 12 The preparation method of the catalyst is basically the same as in Example 2, except that the ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution in step 1 is 6:100.

[0074] Example 13 The preparation method of the catalyst is basically the same as in Example 2, except that the ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution in step 1 is 8:100.

[0075] Example 14 The catalyst preparation method is basically the same as in Example 2, except that the ratio of the number of moles of Ni to the total number of moles of Ni and Cu in the solution in step 1 is 12:100. Example 15 The catalyst preparation method is basically the same as in Example 2, except that in step 1: 1.17 mmol anhydrous copper chloride, 0.13 mmol cobalt chloride hexahydrate, 0.2 g glucose and 1.34 g hexadecylamine are dissolved in 100 mL of ultrapure water to obtain a solution. The ratio of the molar number of Co to the total molar number of Co and Cu is 10:100. The solution is stirred vigorously at room temperature for 12 h until it turns a uniform sky blue color.

[0076] Example 16 The preparation method of the catalyst is basically the same as in Example 15, except that the ratio of the number of moles of Co in the solution in step 1 to the total number of moles of Co and Cu is 1:100.

[0077] Example 17 The preparation method of the catalyst is basically the same as in Example 15, except that the ratio of the number of moles of Co in the solution in step 1 to the total number of moles of Co and Cu is 2:100.

[0078] Example 18 The preparation method of the catalyst is basically the same as in Example 15, except that the ratio of the number of moles of Co in the solution in step 1 to the total number of moles of Co and Cu is 4:100.

[0079] Example 19 The preparation method of the catalyst is basically the same as in Example 15, except that the ratio of the number of moles of Co to the total number of moles of Co and Cu in the solution in step 1 is 6:100.

[0080] Example 20 The preparation method of the catalyst is basically the same as in Example 15, except that the ratio of the number of moles of Co in the solution in step 1 to the total number of moles of Co and Cu is 8:100.

[0081] Example 21 The preparation method of the catalyst is basically the same as in Example 15, except that the ratio of the number of moles of Co to the total number of moles of Co and Cu in the solution in step 1 is 12:100.

[0082] Example 22 The catalyst preparation method is basically the same as in Example 2, except that in step 1: 1.17 mmol anhydrous copper chloride, 0.13 mmol ferric chloride hexahydrate, 0.2 g glucose and 1.34 g hexadecylamine are dissolved in 100 mL of ultrapure water to obtain a solution. The ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 10:100. The solution is stirred vigorously at room temperature for 12 h until it turns a uniform sky blue color.

[0083] Example 23 The preparation method of the catalyst is basically the same as in Example 22, except that the ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 1:100.

[0084] Example 24 The preparation method of the catalyst is basically the same as in Example 22, except that the ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 2:100.

[0085] Example 25 The preparation method of the catalyst is basically the same as in Example 22, except that the ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 4:100.

[0086] Example 26 The preparation method of the catalyst is basically the same as in Example 22, except that the ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 6:100.

[0087] Example 27 The preparation method of the catalyst is basically the same as in Example 22, except that the ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 8:100.

[0088] Example 28 The preparation method of the catalyst is basically the same as in Example 22, except that the ratio of the number of moles of Fe to the total number of moles of Fe and Cu is 12:100.

[0089] Example 29 The catalyst preparation method is basically the same as in Example 2, except that in step 1: 1.17 mmol anhydrous copper chloride, 0.13 mmol zinc chloride hexahydrate, 0.2 g glucose and 1.34 g hexadecylamine are dissolved in 100 mL of ultrapure water to obtain a solution. The ratio of the molar number of Zn to the total molar number of Zn and Cu is 10:100. The solution is stirred vigorously at room temperature for 12 h until it turns a uniform sky blue color.

[0090] Example 30 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 1:100.

[0091] Example 31 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 2:100.

[0092] Example 32 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 4:100.

[0093] Example 33 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 6:100.

[0094] Example 34 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 8:100.

[0095] Example 35 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 12:100.

[0096] Example 36 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 0.5:100.

[0097] Example 37 The preparation method of the catalyst is basically the same as in Example 29, except that the ratio of the number of moles of Zn to the total number of moles of Zn and Cu is 15:100.

[0098] Example 38 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in a 120℃ forced-air oven for 35 h.

[0099] Example 39 The preparation method of the catalyst is basically the same as in Example 1, except for step 2: the solution in step 1 is transferred to a 100 mL polytetrafluoroethylene liner, placed in the reaction vessel and tightened, and reacted in an 80°C forced-air oven for 24 h.

[0100] Comparative Example 1 The preparation method of the catalyst is basically the same as in Example 1, except that anhydrous copper chloride is replaced with anhydrous copper sulfate in step 1.

[0101] Electrochemical activity tests were conducted on different catalysts used in Examples 1 to 39 and Comparative Example 1. Specifically, the tests involved the electrocatalytic reduction of nitric oxide to ammonia using the different catalysts from Examples 1 to 39 and Comparative Example 1. During the experiments, NO gas was introduced into the cathode chamber, and 1 M KOH aqueous solution was introduced into the anode chamber as the electrolyte. A chronoamperometry method was performed for 10 min at a constant potential of -1.0 V. After the test, the electrolyte was collected for product analysis. The ammonia was quantified using the indophenol blue colorimetric method. The results are shown in Table 1.

[0102] Table 1 The basic principles of this disclosure have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in this disclosure are merely examples and not limitations, and should not be considered as essential features of each embodiment of this disclosure. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the scope of this disclosure to the necessity of employing the aforementioned specific details for implementation.

[0103] The above description has been given for purposes of illustration and description. Furthermore, this description is not intended to limit the embodiments of this disclosure to the forms disclosed herein. Although numerous exemplary aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, alterations, additions, and sub-combinations therein.

Claims

1. A catalyst, characterized in that, include: The substrate includes copper nanowires; The doping metal replaces at least a portion of the copper in the copper nanowires, and the doping metal includes transition metals.

2. The catalyst according to claim 1, characterized in that, The copper nanowires are cross-linked to form a network structure; Preferably, the mesh structure encloses at least one hole; Preferably, the size of the pore is 10 nm-100 nm.

3. The catalyst according to claim 1, characterized in that, The transition metal includes at least one of Ni, Co, Fe, and Zn; Preferably, the ratio of the number of moles of the doped metal to the sum of the number of moles of the doped metal and the number of moles of copper is greater than or equal to 1:100 and less than or equal to 12:

100.

4. The catalyst according to claim 1, characterized in that, The length of the copper nanowire is greater than or equal to 5 μm and less than or equal to 8 μm; Preferably, the diameter of the copper nanowire is greater than or equal to 20 nm and less than or equal to 30 nm.

5. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that, include: A precursor solution is obtained by dispersing copper salt, salt of doped metal, reducing agent and surfactant in water; The precursor solution is heated to undergo a first reaction, yielding the catalyst.

6. The preparation method according to claim 5, characterized in that, The copper salt includes anhydrous copper chloride, and the metal-doped salt includes a hydrate of a metal-doped chloride; the reducing agent includes at least one of glucose, ascorbic acid, and ethylene glycol, and the surfactant includes at least one of hexadecylamine, oleylamine, and octadecylamine.

7. The preparation method according to claim 5, characterized in that, The first reaction temperature is greater than or equal to 100℃ and less than or equal to 200℃, and the reaction time is greater than or equal to 12h and less than or equal to 30h.

8. The preparation method according to claim 5, characterized in that, The crude product obtained from the first reaction was centrifuged and washed sequentially to obtain the catalyst; Preferably, the centrifuge speed is greater than or equal to 7000 rpm and less than or equal to 9000 rpm; Preferably, anhydrous ethanol and n-hexane are used for the washing.

9. The preparation method according to claim 8, characterized in that, The washed crude product is dried to obtain the catalyst; Preferably, the drying temperature is greater than or equal to 30°C and less than or equal to 50°C; the drying time is greater than or equal to 10 hours and less than or equal to 14 hours.

10. Use of the catalyst according to any one of claims 1 to 4 in the electrocatalytic reduction of nitric oxide to ammonia.